Heavy metals in river and coast sediments of the Jakarta Bay region (Indonesia) — Geogenic versus anthropogenic sources. Issue 2 (30th September 2016) - Sindern, Sven; Tremöhlen, Martin; Dsikowitzky, Larissa; Gronen, Lars; Schwarzbauer, Jan; Siregar, Tuti Hartati; Ariyani, Farida; Irianto, Hari Eko
Abstract: Sediment geochemistry of the Jakarta region, a densely populated tropical coast, is studied — with particular focus on rivers discharging to Jakarta Bay. Weathering volcanics in the river catchment area control the composition of major elements, As, Cr and in part Cu. In contrast, Zn, Ni, Pb and partly Cu are affected by anthropogenic sources, mainly in central Jakarta City. The data reflect a high variability of local emission sources, among which metal processing industries, fertilizers or untreated animal waste may be important. In particular, the role of street dusts is emphasized. Locally, heavy metals reach levels considered to have adverse biological effects. River discharge leads to anthropogenic enrichment of heavy metals in the coastal sediments. Element data also show geogenic effects on the composition of the coastal sediments, such as mixing of detrital silicates with biogenic carbonates as well as suspended particulate matter from the ocean. Highlights: First regional scale assessment of heavy metals in Jakarta City river sediments Major elements, As and Cr are controlled by volcanic rocks of the catchment area. Zn, Ni and Pb are enriched due to anthropogenic input. Local urban emission sources are characterised by high variability. River discharge leads to anthropogenic heavy metal enrichment in coastal sediments.